Speaking Skill: in Comparison between Extrovert and Introvert Learners - Jajang Setiawan (JOLADU: Journal of Language Education, 2022)
This paper aims to find out the whether introvert students and extrovert students had significant different result in speaking skill, to find out whether the use of memory strategies and social strategies gave significant different result in speaking skill, to investigate whether there was a significant interaction between learning style differences and the use of learning strategies in speaking skill at second semester of computerized program of LP3I Polytechnic Bekasi.. Forty-four students (40) were randomly chosen to get the data of whose styles were extreme introvert and extreme extrovert. Inferential analysis was done by using a two-way ANOVA for hypotheses testing. The research findings showed that there was significant different effect of speaking test between extroverts and introvert. Extroverts performed better in speaking skill. The other finding was that there was not a significant different between using social strategies and memory strategies. As a result of insignificant of using learning strategies in improving speaking skill, it was also found that there was not a significant interaction between language learning style and language learning strategies toward students’ speaking skill.